Geo Shared Licenses: A base for better access to Public Sector Geo-Information for value added resellers in Europe - Welle Donker, Frederika; van Loenen, Bastiaan; Zevenbergen, Jaap (A+BE | Architecture and the Built Environment, 2016)
In a digital age public sector geoinformation (PSGI) is potentially a vital link in the added-value chain. Yet private sector value-added resellers (VARs) still face a number of barriers to using PSGI. Price is only one impediment. The complexity of licences and restrictive licence conditions of PSGI may be an even bigger obstacle. Especially when combining different datasets, VARs can face a quagmire of conflicting licence conditions. Batty (2006 Environment and Planning B: Planning and Design 33 163 – 164) called for research that would stimulate value-added use of PSGI. However, inconsistent and intransparent licence conditions for PSGI are among the biggest obstacles of PSGI for VARs. This paper explores the current PSGI licences to assess the actual restrictions and how current obstacles can be levelled. The Creative Commons licensing concept was explored and adapted to make it suitable for licensing PSGI. The resulting concept of Geo Shared licences is a means to harmonise licence conditions for PSGI. Our research shows that the Geo Shared concept can be a valuable contribution to further harmonisation of PSGI licences and thus development of valueadded chains. Furthermore, development of geographic information infrastructures will also be stimulated. Similarly, the concept can be considered as a serious option within the Infrastructure of Spatial Information for Europe (INSPIRE), as a way towards transparent harmonised licences in Europe and beyond.